In memoriam: GARY BECKER - Tsaoussi, Aspasia (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2016)
This essay commemorates Nobel Laureate Gary Becker, one of the most prominent and iconoclastic economists of the 20th century. At the same time, it is written with the utmost gratitude felt by a student for her teacher. Becker served as the chairman of my dissertation committee at the University of Chicago Law School in the years 1995-2000.